Innovations in Marketing Management of Islamic Banks Facing Global Market Challenges in Jayapura - Salima Rumatoras; Fitriani Fitriani; Nani Hanifah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
As we know, Sharia Banking in Jayapura faces various challenges in an ever-changing global market such as awareness and understanding, regulations, competition, product and service development, and human resources. However, with the right product innovation, Sharia banking can remain competitive and even lead in the banking industry. By focusing on product diversification, Sharia-based technology, financial inclusivity and education, Sharia banking can continue to respond to global market challenges and serve society better. Product innovation is key to achieving goals and ensuring sustainable growth of Sharia banking in the future. The Sharia banking market is facing increasingly tight competition with conventional banks. Conventional banks are increasingly adopting Sharia banking principles in their products, thereby increasing competition in the market. Changes in sharia banking regulations continue to develop in Jayapura, and these changes can affect Sharia banking operations and products.